Work stress and its influence on the work performance of Swaziland teachers in the Swaziland school education system - Hamid, Zaheer; Bisschoff, Christo; Botha, Christoff (Kamla Raj Enterprises, 2015)
This paper deals with work stress within the Swaziland school education context. The objectives are to examine, understand, identify causes of workplace stress and examine how influences work performance. The discussion includes how unmanaged and/or unidentified it manifests itself in relation to the health, welfare and abilities of workers, specifically relating to Swaziland school teachers. The workplace stress-related factors of the teachers and how it influences their work performance were examined using a stratified random sample to identify respondents to complete the structured questionnaire (N = 750; n=368) in the Mbabane, Manzini and Ezulwini areas. Nine factors, explaining a cumulative variance of 56.5 percent, were identified using exploratory factor analysis These factors are (in declining order of importance) Satisfaction, Unfair promotion, Internal locus of control, Job performance, Personal growth, Job retention, Job loyalty, Competence and Job control.
Keywords: Educator; Manager; Public school; Stress stimulus; Stressors